The FIFA medical emergency bag and FIFA 11 steps to prevent sudden cardiac death: setting a global standard and promoting consistent football field emergency care - Dvorak, J.; Kramer, E. B.; Schmied, C. M.; Drezner, J. A.; Zideman, D.; Patricios, J.; Correia, L.; Pedrinelli, A.; Mandelbaum, B. (British Journal of Sports Medicine, 2013)
Life-threatening medical emergencies are an infrequent but regular occurrence on the football field. Proper prevention strategies, emergency medical planning and timely access to emergency equipment are required to prevent catastrophic outcomes. In a continuing commitment to player safety during football, this paper presents the FIFA Medical Emergency Bag and FIFA 11 Steps to prevent sudden cardiac death. These recommendations are intended to create a global standard for emergency preparedness and the medical response to serious or catastrophic on-field injuries in football.